2022
DOI: 10.4103/jdmimsu.jdmimsu_78_22
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Metabolic Syndrome in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Introduction: This observational study was done to study the patients having metabolic syndrome with chronic obstructive pulmonary disease (COPD). Methodology: A cross-sectional observational study was done which included all the patients having COPD by convenience sampling presented at the Respiratory Medicine Department in Acharya Vinoba Bhave Rural Hospital, a tertiary hospital in Sawangi (Meghe), Wardha, India, from November 2021 to January 2022. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In contrast, Ghatas [15] determined the prevalence to be nearly identical to ours, at 42.60%. Meanwhile, Ali et al [16] discovered that it was 57.1%. Breyer's [13] research revealed that hyperglycemia is the most common MetS component among COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ghatas [15] determined the prevalence to be nearly identical to ours, at 42.60%. Meanwhile, Ali et al [16] discovered that it was 57.1%. Breyer's [13] research revealed that hyperglycemia is the most common MetS component among COPD patients.…”
Section: Discussionmentioning
confidence: 99%